2019
DOI: 10.1093/gbe/evz176
|View full text |Cite
|
Sign up to set email alerts
|

Multilayered Tuning of Dosage Compensation and Z-Chromosome Masculinization in the Wood White (Leptidea sinapis) Butterfly

Abstract: In species with genetic sex determination, dosage compensation can evolve to equal expression levels of sex-linked and autosomal genes. Current knowledge about dosage compensation has mainly been derived from male-heterogametic (XX/XY) model organisms, whereas less is understood about the process in female-heterogametic systems (ZZ/ZW). In moths and butterflies, downregulation of Z-linked expression in males (ZZ) to match the expression level in females (ZW) is often observed. However, little is known about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 90 publications
1
11
0
Order By: Relevance
“…The main factor affecting global expression profiles across all samples was developmental stage, whereas no effect of sex could be detected. This is in line with previous studies that found considerable differences in gene expression profiles between ontogenetic stages (Leal et al, 2018), but only a small proportion of sex-biased genes in the larval stages (Höök et al, 2019). We did not observe any obvious clustering by either population or host plant treatment, in contrast to other studies where different host plant use results in clearly distinguishable expression profiles (Celorio-Mancera et al, 2013).…”
Section: Gene Expression Variation Across Populations and Experimensupporting
confidence: 92%
See 2 more Smart Citations
“…The main factor affecting global expression profiles across all samples was developmental stage, whereas no effect of sex could be detected. This is in line with previous studies that found considerable differences in gene expression profiles between ontogenetic stages (Leal et al, 2018), but only a small proportion of sex-biased genes in the larval stages (Höök et al, 2019). We did not observe any obvious clustering by either population or host plant treatment, in contrast to other studies where different host plant use results in clearly distinguishable expression profiles (Celorio-Mancera et al, 2013).…”
Section: Gene Expression Variation Across Populations and Experimensupporting
confidence: 92%
“…Finally, fastq Screen (Wingett, 2017) with bowtie2 version 2.3.5 (Langmead & Salzberg, 2012) was used to identify and screen for contaminants. The most likely contaminants were identified based on previous gene expression studies in L. sinapis (Höök et al, 2019;Leal et al, 2018). The filtered data set was screened for contaminants of the following origin: rRNA, human, Drosophila…”
Section: Gene Expression Profilingmentioning
confidence: 99%
See 1 more Smart Citation
“…sinapis (Höök et al, 2019), can therefore be a potential reason for the much more conserved Z chromosomes. The fact that the Z chromosome only recombines and spends relatively more time in male butterflies (Turner & Sheppard, 1975) should further strengthen this linkage.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the Z chromosome only recombines and spends relatively more time in male butterflies (Turner & Sheppard, 1975) should further strengthen this linkage. Translocation of genes from the sex chromosomes might also be selected against if it alters expression levels regulated by dosage compensation mechanisms, which has been observed in L. sinapis (Höök et al, 2019).…”
Section: Discussionmentioning
confidence: 99%